A broadband cavity ringdown spectrometer for in-situ measurements of atmospheric trace gases - Bitter, M.; Ball, S. M.; Povey, I. M.; Jones, R. L. (HAL CCSD, 2005)
International audience This paper describes a broadband cavity ringdown spectrometer and its deployment during the 2002 North Atlantic Marine Boundary Layer Experiment (NAMBLEX) to measure ambient concentrations of NO 3 , N 2 O 5 , I 2 and OIO at the Mace Head Atmospheric Research Station, Co. Galway, Ireland. The effective absorption path lengths accessible with the spectrometer generally exceeded 10 km, enabling sensitive localised ''point'' measurements of atmospheric absorbers to be made adjacent to the other instruments monitoring chemically related species at the same site. For the majority of observations, the spectrometer was used in an open path configuration thereby avoiding surface losses of reactive species. A subset of observations targeted the N 2 O 5 molecule by detecting the additional NO 3 formed by the thermal dissociation of N 2 O 5 . In all cases the concentrations of the atmospheric absorbers were retrieved by fitting the differential structure in the broadband cavity ringdown spectra using a methodology adapted from long path differential optical absorption spectroscopy. The uncertainty of the retrieval depends crucially on the correct treatment and fitting of the absorption bands due to water vapour, a topic that is discussed in the context of analysing broadband cavity ringdown spectra. The quality of the measurements and the retrieval method are illustrated with representative spectra acquired during NAMBLEX in spectral regions around 660 nm (NO 3 and N 2 O 5 ) and 570 nm (I 2 and OIO). Typical detection limits were 1 pptv for NO 3 in an integration time of 100 s, 4 pptv for OIO and 20 pptv for I 2 in an integration time of 10 min. Additionally, the concentrations of atmospheric water vapour and the aerosol optical extinction were retrieved in both spectral regions. A companion paper in this issue presents the time series of the measurements and discusses their significance for understanding the variability of short lived nitrogen and iodine compounds in the marine boundary layer.